PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM PADA PENDIDIKAN TINGGI - Arifin, Samsul (AN NAHDLIYYAH, 2024)
This study aims at finding the development of Islamic education curriculum in higher education. curriculum development conceived as an effort to develop a curriculum that refers to the Indonesian Qualifications Framework (KKNI), National Standards for Higher Education (SNPT), and Paradigm Integration-Interconnection Studies as the orientation of scientific development at STAINU Malang. This study was conducted by means of naturalistic qualitative approach. The location of this study was at the Department of Islamic Religious Educatioan of Faculty of Islamic Education and Teaching STAINU Malang. The subjects consisted of cases which are selected by purposive sampling techniques. The study procedure of collecting data consisted of four steps: observation, in-depth interviews, and document study. The data were analyzed using inductive models, while the validity of the result met the criteria of credibility, transferability, dependability and conformability. The research findings are as follows: first, the emphasis on curriculum development (a) clarity profile of graduates with a description of its operation. (b) The learning outcomes as an indicator graduate profile that refers to KKNI and SNPT. (c) Field studies as a strategic issue which combined with the development of the course learning outcomes, (d) Half the weight of the unit credits obtained by multiplying the depth and breadth of study material; Second, the development of the curriculum to accommodate all the requirements of a professional teacher with four competencies; pedagogical, personality, social and professional competence, plus the competence of the leadership. Third, curriculum development in MPI Department also stressed on the aspect of MPI consisting of Al-Qur’an Hadith, Aqidah Akhlak, Fiqh, Sejarah Kebudayaan Islam to improve the professional competence of future teachers.